2023
DOI: 10.1021/acsomega.3c00222
|View full text |Cite
|
Sign up to set email alerts
|

Single Inhibitors versus Dual Inhibitors: Role of HDAC in Cancer

Abstract: Due to the multimodal character of cancer, inhibition of two targets simultaneously by a single molecule is a beneficial and effective approach against cancer. Histone deacetylase (HDAC) was widely investigated as a novel category of anticancer drug targets due to its crucial role in various biological processes like cell-proliferation, metastasis, and apoptosis. Numerous HDAC inhibitors such as vorinostat and panobinostat are clinically approved but have limited usage due to their low efficacy, nonselectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Based on the earlier findings, the designed dual HDAC/EGFR inhibitors acquire the following pharmacophoric features: (a) 2methylquinazoline main scaffold acting as a capping group in HDAC inhibitors and to occupy the ATP binding site for EGFR inhibition, (b) phenoxy moiety acts as a linker for HDAC inhibition and to occupy the hinge region of EGFR, (c) chalcone moiety which could act as a common ZBG for HDAC inhibition and may offer an additional binding interaction for inhibition of EGFR enzyme and, otherwise their powerful role in induction of apoptosis, and (d) hydrophobic tail to occupy the hydrophobic pocket of EGFR. [31,40] Employing molecular hybridization to connect the 2-methylquinazoline and chalcone moieties through an oxygen linker, compounds 5a-e were designed to act as dual inhibitors for HDAC and EGFR TK.…”
Section: Rationale and Designmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the earlier findings, the designed dual HDAC/EGFR inhibitors acquire the following pharmacophoric features: (a) 2methylquinazoline main scaffold acting as a capping group in HDAC inhibitors and to occupy the ATP binding site for EGFR inhibition, (b) phenoxy moiety acts as a linker for HDAC inhibition and to occupy the hinge region of EGFR, (c) chalcone moiety which could act as a common ZBG for HDAC inhibition and may offer an additional binding interaction for inhibition of EGFR enzyme and, otherwise their powerful role in induction of apoptosis, and (d) hydrophobic tail to occupy the hydrophobic pocket of EGFR. [31,40] Employing molecular hybridization to connect the 2-methylquinazoline and chalcone moieties through an oxygen linker, compounds 5a-e were designed to act as dual inhibitors for HDAC and EGFR TK.…”
Section: Rationale and Designmentioning
confidence: 99%
“…[ 54–56 ] The study demonstrated that merging quinazoline core with ZBGs via a suitable linker could surmount tumor relapse and drug resistance. [ 35,57 ] HDAC/EGFR dual inhibitors with the aim of discovering potent antitumor agents showed promising results in combating the nonselectivity and drug resistance problems associated with single‐target drugs. [ 31 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Noticeably, normal cells are usually more resistant than tumor cells to HDACIs. [24][25][26][27] The combination of HDACIs as chemosensitizers with other cancer therapeutics has shown great potential in preclinical and therefore clinical trials and may represent a way to achieve complete therapeutic benefits. [28][29][30][31][32] Different HDAC inhibitors have already been linked in the axial positions of Pt(IV) cores, showing synergistic activity with Pt(II) metabolites.…”
Section: Introductionmentioning
confidence: 99%